Proceedings of the 5th International Symposium on Principles and Practice of Programming in Java - PPPJ '07 2007
DOI: 10.1145/1294325.1294353
|View full text |Cite
|
Sign up to set email alerts
|

Towards intelligent analysis techniques for object pretenuring

Abstract: Object pretenuring involves the identification of long-lived objects at or before their instantiation. It is a key optimization for generational garbage collection systems, which are standard in most high performance Java virtual machines. This paper presents a new study of factors that are used to indicate object lifespans. We adopt the information theory measurement of normalized mutual information to compare these various different factors in a common framework. A study of garbage collection traces from fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…although the ckjm tool has been also used in other work (e.g. [13]) and is trusted, differences in the measurement values have been reported [14]. We plan to investigate the results with other tools, specially if there are differences between tools using the source or compiled code as is the case of ckjm.…”
Section: Construct Validitymentioning
confidence: 99%
“…although the ckjm tool has been also used in other work (e.g. [13]) and is trusted, differences in the measurement values have been reported [14]. We plan to investigate the results with other tools, specially if there are differences between tools using the source or compiled code as is the case of ckjm.…”
Section: Construct Validitymentioning
confidence: 99%
“…In [25] the pretenuring classification is based on a program analysis which identifies patterns of lifetime behavior and compares them against a database of previous knowledge of socalled micro-patterns [12]. [32] studied more advanced classification schemes for pretenuring, considering metrics beyond allocation sites, such as types. Static techniques, offline techniques, and dynamic techniques based on training data have the advantage of low runtime overhead but require prior knowledge of application behavior and cannot react to dynamic feedback.…”
Section: Related Workmentioning
confidence: 99%
“…[26][27][28][29]). Hirzel et al studied a suite of benchmarks and concluded that object connectivity correlates strongly with object lifetime [30].…”
Section: Profilingmentioning
confidence: 99%
“…Contrasting with this, others have shown how stack state at the point of object allocation correlates with object lifetime [31]. Singer et al studied a small benchmark suite in an effort to identify good predictions of long-lived objects [29]. Chen et al consider the lifetime of object fields, rather than whole objects, since a field may not be active for the duration of its enclosing object's life; thus, fields with disjoint lifetimes can occupy the same memory, thereby reducing object footprint [32].…”
Section: Profilingmentioning
confidence: 99%